Adverse childhood experiences and sleep links in a predominantly Black sample of overweight adults. (9th July 2022) - Rojo‐Wissar, Darlynn M.; Reid, Matthew J.; Burton, Emily; Sosnowski, David W.; Smith, Michael T.; Coughlin, Janelle W.; Spira, Adam P.; Salwen‐Deremer, Jessica K.
Abstract: Adverse childhood experiences (ACEs) have been associated with worse sleep, but existing literature is limited by use of predominantly White samples, lack of objective sleep measurement, and use of non‐standardized questionnaires. We investigated associations between retrospectively reported ACEs and sleep in adulthood in a sample of 43 adults 20–53 years of age, free from chronic conditions, with a Body mass index (BMI) ≥ 25 (Mean age = 33.14 [SD = 10.05], 74% female, 54% Black). Sleep efficiency (SE), total sleep time (TST), wake after sleep onset (WASO), and sleep onset latency (SOL), were measured by actigraphy and daily diary. Global sleep quality and insomnia severity were measured by questionnaires. Sleepiness, fatigue, and sleep quality were also measured by daily diary. Adjusting for demographic characteristics and BMI, ACEs were significantly associated with poorer global sleep quality and diary measures of greater daytime sleepiness, fatigue, and poorer sleep quality. There were no significant associations between ACEs and SE, TST, WASO, or SOL measured by diary or actigraphy. Findings suggest that ACEs are associated with worse sleep perception and daytime functioning in adulthood. Larger prospective studies are needed to replicate these findings, examine racial/ethnic differences, and determine temporal associations between ACEs, sleep, and health (e.g., BMI).